KETENTUAN HUKUM DALAM KELUARAN 22:6-8 TENTANG KEHIDUPAN BERSAMA MENGENAI HARTA KEPEMILIKAN - Abraham Pakpahan (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
The Israel community is a community that has a close relationship with one another. To regulate the life of this community, of course, a legal provision is applied to regulate the life of the Israel community. The Covenant Code Agreement (Ex. 22:6-8) are provisions that regulate property that is lost or stolen when the item is entrusted to another person. The Covenant Code in this text have case examples that illustrate the conflicts that occurred until the resolution of the problem in this case. The cases that occur in the text specifically provide cases of steps to resolve conflicts between people to prevent relationships that have the potential to be damaged due to loss of property. The purpose of this research is to understand the text with a more specific case when compared to Ex. 20:15 (decalog ‘not steal’). This research was carried out using a literature study using a critical historical approach and arrived at the conclusion that when someone has been given responsibility, the responsibility is not only towards each other but also towards God and to build harmonious relationships with others.